INTELLEGENT AUTOMATION IT OPERATIONINTEGRATION OF AIOPS AND VOICE CONTROL SYSTEMS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article examines approaches to automating IT infrastructure management using AIOps (Artificial Intelligence for IT Operations) technologies. The architecture, key tools, application areas, advantages, and limitation of implementing AIOps platforms are analyzed. Particular attention is paid to the use of machine complex. for monitoring, event analysis, and predictive infrastructure management.